Bargaining for Compensation in the Shadow of Regulatory Giving: The Case of Stock Trading Rights Reform in China - Chen, Jian-Lin; Wang, Wallace Wen-Yeu (Columbia Journal of Asian Law, 2006)
The split share structure’ is a unique Chinese phenomenon that has plagued its capital markets. It arose out of classifying shares based on ownership whereby only certain types of shares were allowed to trade on the Chinese exchanges. The remaining types, constituting the majority of shares, were not allowed to trade and could only be transferred privately.2 This non-trading of the bulk of shares resulted in severe market deficiencies, such as conflicts of interest between the non-tradable shareholders3 and tradable shareholders, erosion of the capital market pricing mechanism and problems in corporate governance. While it is not the sole cause, the split share structure certainly has contributed significantly to the poor performance of the Chinese markets.